2008
DOI: 10.1055/s-0028-1090594
|View full text |Cite
|
Sign up to set email alerts
|

The Ductus Arteriosus Rarely Requires Treatment in Infants > 1000 Grams

Abstract: We sought to determine the rate of spontaneous closure of the ductus arteriosus (DA) in very-low-birth-weight infants. This prospective observational study included 65 infants whose birth weight (BW) < 1500 g. Echocardiograms were done on day of life (DOL) 3 and 7, weekly for the first month, and bimonthly until ligation, discharge, or death. Treatment was reserved for infants with heart failure, acute renal impairment, or those with significant persistent or escalating respiratory support. Chi-square tests, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 30 publications
8
109
0
3
Order By: Relevance
“…131 Spontaneous closure rates, particularly after 7 days of age, may be underestimated, as the majority of infants included in these reports were treated by the second week after birth. In a prospective observational study of 65 very low birth weight (<1500 g) infants, Nemerofsky et al 132 found spontaneous ductal closure by 7 days of age in 31% of those with birth weights p1000 g and in 67% of those with birth weights >1000 g. For those with BWp1000 g, spontaneous closure without intervention occurred before discharge in 47% (at a median age of 56 days); one infant was treated with indomethacin in the first week and the remaining 16 had treatment initiated at a median age of 14 days. Among the larger infants (BW>1000 g), no intervention was required in 97% and the ductus spontaneously closed before discharge in 94% (at a median age of 7 days).…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%
See 1 more Smart Citation
“…131 Spontaneous closure rates, particularly after 7 days of age, may be underestimated, as the majority of infants included in these reports were treated by the second week after birth. In a prospective observational study of 65 very low birth weight (<1500 g) infants, Nemerofsky et al 132 found spontaneous ductal closure by 7 days of age in 31% of those with birth weights p1000 g and in 67% of those with birth weights >1000 g. For those with BWp1000 g, spontaneous closure without intervention occurred before discharge in 47% (at a median age of 56 days); one infant was treated with indomethacin in the first week and the remaining 16 had treatment initiated at a median age of 14 days. Among the larger infants (BW>1000 g), no intervention was required in 97% and the ductus spontaneously closed before discharge in 94% (at a median age of 7 days).…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%
“…Pragmatism dictates incremental movement in that direction. Nemerofsky et al 132 have suggested an excellent initial strategy: refrain from treatment altogether in infants with birth weights >1000 g and defer treatment until at least the second week after birth in smaller infants. The available evidence indicates that this will substantially reduce the number of infants subjected to potential adverse effects of treatment without incurring an incremental risk of untoward long-term outcomes.…”
Section: Patent Ductus Arteriosus We Benitzmentioning
confidence: 99%
“…[24][25][26][27][28] A second one is that, with time, an important number of PDA's close spontaneously. [29][30][31] The third one is that this clinical condition has a wide range of severity. There are many infants in whom PDA's have no clinical significance, whereas others may have severe ventricular insufficiency and pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no randomized controlled trials comparing the 3 different approaches, and there is an ongoing debate regarding the ideal treatment of PDA in preterm infants 9) . Because the rate of spontaneous ductus closure in infants weighing <1,000 g is very high, 35% by 6 days after birth, 67% by 7 days after birth, and 94% before hospital discharge, hemodynamically insignificant patent ductus arteriosus seldom requires treatment 10,11) . There fore, the treatment guidelines should be based on the clinical manifestations of hemodynamically significant PDA and tolerance in preterm infants, rather than focusing on the PDA itself.…”
Section: Introductionmentioning
confidence: 99%
“…There fore, the treatment guidelines should be based on the clinical manifestations of hemodynamically significant PDA and tolerance in preterm infants, rather than focusing on the PDA itself. Recently, supportive approach has become more common, and pharmacologic and surgical treatments are less commonly used 9,12) , but evidence supporting the treatment approaches is insufficient and the risks are not clear 9,10,13) . The brains of preterm infants achieve rapid growth during the premature period after birth, and are more vulnerable to various stresses 14,15) ; therefore, PDA still remains a risk factor for PVL, IVH, and white matter damage.…”
Section: Introductionmentioning
confidence: 99%